2014
DOI: 10.2337/db13-1042
|View full text |Cite
|
Sign up to set email alerts
|

Deoxysphingolipids, Novel Biomarkers for Type 2 Diabetes, Are Cytotoxic for Insulin-Producing Cells

Abstract: Irreversible failure of pancreatic β-cells is the main culprit in the pathophysiology of diabetes, a disease that is now a global epidemic. Recently, elevated plasma levels of deoxysphingolipids, including 1-deoxysphinganine, have been identified as a novel biomarker for the disease. In this study, we analyzed whether deoxysphingolipids directly compromise the functionality of insulin-producing Ins-1 cells and primary islets. Treatment with 1-deoxysphinganine induced dose-dependent cytotoxicity with senescent,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
101
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 111 publications
(109 citation statements)
references
References 40 publications
6
101
1
1
Order By: Relevance
“…30 Elevated plasma 1-deoxySLs were also found in patients with metabolic diseases such as the MetS and T2DM and might be directly involved in the development of insulin resistance. 20 However, the increased 1-deoxySL formation in metabolic diseases is not caused by mutations in SPT but is associated with a derailed carbohydrate and fatty acid metabolism. In several previous studies, we observed a strong correlation between plasma 1-deoxySLs and triglyceride levels, which raised the question whether increased TG levels are confounders for elevated 1-deoxySL.…”
Section: Discussionmentioning
confidence: 99%
“…30 Elevated plasma 1-deoxySLs were also found in patients with metabolic diseases such as the MetS and T2DM and might be directly involved in the development of insulin resistance. 20 However, the increased 1-deoxySL formation in metabolic diseases is not caused by mutations in SPT but is associated with a derailed carbohydrate and fatty acid metabolism. In several previous studies, we observed a strong correlation between plasma 1-deoxySLs and triglyceride levels, which raised the question whether increased TG levels are confounders for elevated 1-deoxySL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, 1-deoxySLs were shown to be elevated under Taxol treatment and might contribute to Taxol-induced peripheral neuropathy (13). Furthermore, 1-deoxySLs were found to be increased in patients with nonalcoholic steatohepatitis (14) and to interfere with the function and survival of pancreatic -cells (15). Elevated 1-deoxySL plasma levels are also predictive for the risk to develop T2D (6).…”
Section: Extraction and Analysis Of Sphingoid And Deoxysphingoid Basesmentioning
confidence: 93%
“…The development sphinganine is acylated to dihydroceramides that in turn are desaturated to ceramides; therefore, these dihydrosphingolipids typically refl ect the status of de novo sphingolipid biosynthesis rather than turnover ( 54 ). Elevations in 1-deoxy-sphingolipids are also refl ective of altered biosynthesis because they are produced when there is a shift in the availability of alanine versus serine, as both are utilized by serine palmitoyltransferase ( 54 ), and have been associated with diabetes ( 55 ). The mRNA level of SPTLC1 is unchanged and SPTLC2 was not detected in transcriptomic data.…”
Section: Discussionmentioning
confidence: 99%